2016
DOI: 10.1002/bit.26226
|View full text |Cite
|
Sign up to set email alerts
|

In vitro suppression of two different stop codons

Abstract: Proteins play a crucial role in all living organisms, with the 20 natural amino acids as their building blocks. Unnatural amino acids are synthetic derivatives of these natural building blocks. These amino acids have unique chemical or physical properties as a result of their specific side chain residues. Their incorporation into proteins through ribosomal translation in response to one of the stop codons has opened a new way to manipulate and study proteins by enabling new functionalities, thus expending the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…One of the most widely used protocols for extract preparation is the S30 protocol [13,18,24,[27][28][29][30][31][32], which was modified in this study to create the genetically expanded cell-free protein synthesis system. When using orthogonal translation systems (OTS) to achieve GCE harbored on a replicating bacterial vector, such as the pEVOL [33] vector, the extract preparation protocol becomes much longer and more difficult as the bacterial growth becomes slower.…”
Section: Simplified Extract Preparation and Cell-free Reaction For Gementioning
confidence: 99%
See 4 more Smart Citations
“…One of the most widely used protocols for extract preparation is the S30 protocol [13,18,24,[27][28][29][30][31][32], which was modified in this study to create the genetically expanded cell-free protein synthesis system. When using orthogonal translation systems (OTS) to achieve GCE harbored on a replicating bacterial vector, such as the pEVOL [33] vector, the extract preparation protocol becomes much longer and more difficult as the bacterial growth becomes slower.…”
Section: Simplified Extract Preparation and Cell-free Reaction For Gementioning
confidence: 99%
“…Recently, we have found that extracts from the same bacterial strain but with different genotypes and from different batches could be mixed and combined [13], this led us to develop a modular approach for cell-free protein synthesis with GCE. In this approach, a component of choice, which could be a protein or a non-protein-coding gene like tRNAs, could be expressed separately in bacteria which will sequentially be prepared as an extract that contains the said The results clearly show that this approach is viable for at least four different combinations of interacting components of tRNAs and tRNA synthetases.…”
Section: A Modular Approach To Cell-free Protein Synthesis With Uaasmentioning
confidence: 99%
See 3 more Smart Citations